Further understanding of Pseudomonas aeruginosa's ability to horizontally acquire virulence: possible intervention strategies. Issue 6 (2nd June 2020) - Redfern, James; Enright, Mark C.
ABSTRACT: Introduction: Pseudomonas aeruginosa is a common, ubiquitous bacterium that is found in natural environments but is also a successful opportunistic pathogen of humans and plants. The reasons for this flexibility and evolutionary success can be attributed to its ability to readily acquire new genes to ensure its survival enabling it to survive desiccation, the action of antimicrobial compounds and invade new territories such as modern hospitals with high levels of antibiotic usage. Areas covered: Literature was searched using PubMed and Web of science (05/19 to 05/20). Identified studies paint a picture of a dynamic, highly variable population shaped by frequent intra- and inter-species horizontal gene transfer resulting in a species able to resist the action of antibiotics and deploy multiple virulence strategies controlled by complex quorum-sensing systems. We investigate possible control measures including anti-virulence and environmental control measures. Expert opinion: P. aeruginosa is a resilient, richly diverse species but also a global health threat due to the emergence and global dissemination of successful multiresistant clones that resist all antibiotics. Genomics offers the potential for rapid identification of 'high-risk' clones to guide chemotherapy, but novel control measures are also required to slow the species progression to pan-resistance.